Hexa-Helix Stakeholder Collaboration in the Development of Tourism and Creative Economy Based on Local Wisdom - TODA, Hendrik; NIGA, Jacoba Daud; RIHI, David Wilfrid; PENI, Andreas A.; LINO, Maria M (PT Keberlanjutan Strategis Indonesia, 2024)
The tourism sector is the sector that has the most significant contribution in the world in every country. This research aims to examine and analyze the implementation of the hexa-helix principle in developing the tourism business and creative economy in West Sumba. The research was conducted using a descriptive qualitative model. The data collection method used interview and documentation mechanisms, then analyzed using triangulation-based qualitative methods. The results are classified, and coding is carried out to formulate data validation and reliability. This research found that academics, society and tourists answer that tourism in West Sumba has met the requirements in the context of education, meeting community needs and can attract quality tourists and has an impact on increasing local revenue. However, the hexa-helix concept in government, mass media and the business world is still being adjusted and needs to be fully operational. So, it has not reached the optimal level for marketing and developing sustainable tourism infrastructure.